The relationship between paediatric antibiotic misuse and recurrent acute respiratory tract infection - Ayad, Zahraa M.; Al-Ameedi, Ali I.; Hajwal, Salim K.; Al-Taee, Mahdi Hamzah; Hassan, Abbas Abdul-Hussein; Khaleel, Muna Abdulwahab; Muhaibes, Fakhria Jaber; Abbas, Alaa Hamza; Ridha-Salman, Hayder (Pharmakeftiki, 2025)
Antimicrobial resistance (AMR) represents one of the most pressing challenges in contemporary public health. Neonates and children are among the most vulnerable populations, not only by being at heightened risk of developing AMR, but also for being among the ones most frequently being prescribed antibiotics, particularly for respiratory tract infections (RTIs). This study aimed at examining the relationship between antibiotic overuse and resistance in paediatric patients with recurrent RTIs. A descriptive cross-sectional design was employed from 10 December 2023 to 10 March 2024, targeting children in the Babil Province (Iraq) that were selected through a non-probability convenience sampling method. Findings revealed a high prevalence of antibiotic prescription errors: 62% of the cases involved inadequate course duration, 69% of the patients received duplicate therapy, and 61% were prescribed antibiotics with insufficient dosing frequency. A significant association was observed between these prescription errors and a history of recurrent RTIs. Such errors appear to contribute to the development of AMR, not only in children but potentially extending to adult populations. Given the potentially fatal consequences of antibiotic misuse, both paediatricians and parents must exercise rigorous caution when administering antibiotics to children.